Per un progetto sui dipinti firmati di Venezia in età gotica e tardogotica - Riccioni, Stefano (Venezia Arti, 2017)
The paper provides a brief examination of Lorenzo Veneziano signatures as first step of a research project which aims at gathering and examining on the signature-inscriptions on paintings by the Venetian painters and the painters who worked in Venice in the Gothic age (XIIIth century-early decades of XVth century). The study of the inscriptions will be conducted with an interdisciplinary approach, joining art-history, paleography and philology in a historic, critic and social perspective so as to achieve a better comprehension of the emergence of the artist’s figure and name on the works of art as well as in the society; the methods of production of paintings and the organization of workshops;  the literacy and ‘culture’ of the artists and their relationship with the world of the written word; the birth of a biographical and professional ‘memory’ and self-consciousness; The technical and critical vocabulary of medieval artistic culture.